Examining The Financial Returns Of CSR In The Palm Oil Sector : Insights From a Systematic Literature Review - Yuhendra, Alfis; Atikah, Qhisthina; Yusdiana, Yusdiana; Juliaviani, Noratun; Zaputra, Aris (Jurnal Agrisep, 2025)
The palm oil industry plays a crucial role in the global economy but faces complex environmental and social challenges. This study aims to analyze how Corporate Social Responsibility (CSR) practices contribute to the financial performance of palm oil companies, particularly in terms of profitability, financial risk management, and operational efficiency. Using the Systematic Literature Review (SLR) method and data analysis supported by Atlas.ti software, this research reviewed 20 peer-reviewed articles published between 2019 and 2024. The findings reveal that sustainability-oriented CSR consistently improves operational efficiency, especially through better resource management and adherence to industry standards. Moreover, CSR plays a role in reducing financial risks, primarily by enhancing investor trust and regulatory stability. However, while there are signs of a connection between CSR and profitability, this relationship remains limited in the reviewed literature, indicating the need for more strategic integration of CSR into core business operations. These results affirm that CSR is not merely a form of social responsibility, but a strategic instrument to strengthen competitiveness, resilience, and long-term performance in the palm oil industry amid growing global sustainability pressures.